Modeling the impact of evolving biofilms on flow in porous media inside a microfluidic channel. (1st January 2021) - Karimifard, Shahab; Li, Xu; Elowsky, Christian; Li, Yusong
Highlights: Hydrodynamics of porous media are highly dependent on biofilm permeability. Biofilm porosity cannot be neglected with intermediate and high levels of biofilm. Simplified biofilm geometries can be used when biofilm levels are high. Abstract: This study integrates microfluidic experiments and mathematical modeling to study the impacts of biofilms on flow in porous media and to explore approaches to simplify modeling permeability with complicated biofilm geometries. E. coli biofilms were grown in a microfluidic channel packed with a single layer of glass beads to reach three biofilm levels: low, intermediate, and high, with biofilm ratios ( βr ) of 2.7%, 17.6%, and 55.2%, respectively. Two-dimensional biofilm structures and distributions in the porous medium were modeled by digitizing confocal images and considering broad ranges of biofilm permeability ( kb ) (from 10 −15 m 2 to 10 −7 m 2 ) and biofilm porosity ( εb ) (from 0.2 to 0.8). The overall permeability of the porous medium ( k ), the flow pathways and the overall/local pressure gradients were found to be highly dependent on βr and kb but were moderately impacted by εb when the biofilm levels were high and intermediate with kb >10 −11 m 2 . When biofilm structures are well developed, simplified biofilm geometries, such as uniform coating and symmetric contact filling, can provide reasonable approximations of k . Graphical abstract: Image, graphical abstract